Direct comparisons between hypnosis and meditation: A mini-review - Penazzi, Gabriele; De Pisapia, Nicola (Frontiers in Psychology, 2022)
Hypnosis and meditation share phenomenological and neurophysiological features, and their comparison is a topic of growing interest in the scientific literature. In this article, we review a classification of these two kinds of non-ordinary states of consciousness, and discuss the studies that directly compare them. Some findings seem to suggest that hypnosis and meditation are distinct phenomena, while others underline their similarities, but experiments that directly contrast them are still scarce and no consensus has been reached yet. While this comparison could give us fundamental insights into central issues concerning the role of attention, metacognition and executive control in the study of consciousness, it is clear that we are still at the early stages of this research.